Answer :

Sum of GP for n terms S1 =


= …(1)


Sum of GP for 2n terms S2 =


= …(2)


Sum of GP for 3n terms S3 = …(3)


=


Let


1, 2 and 3 becomes


S1 = K(rn - 1)


S2 = K(r2n - 1)


S3 = K(r3n - 1)


S12 + S22 = k2(rn - 1)2 + k2(r2n - 1)2


= k2(r2n + 1 - 2.rn + r4n + 1 - 2.r2n)


= k2(r4n - r2n - 2rn + 2)


L.H.S = k2(r4n - r2n - 2rn + 2)


S1(S2 + S3) = K(rn - 1)[ (K(r2n - 1) + K(r3n - 1))]


= K2(rn - 1)[r2n + r3n - 2]


= k2(r4n - r2n - 2rn + 2)


Hence, Proved.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

A person has 2 paRD Sharma - Mathematics

The sum of the seRD Sharma - Mathematics

How many terms ofRD Sharma - Mathematics

If <span lang="ENRD Sharma - Mathematics

Let anRD Sharma - Mathematics

Find the sum of 2RD Sharma - Mathematics

If <span lang="ENRS Aggarwal - Mathematics

Find the sum (41 RS Aggarwal - Mathematics

Find the sum (2 +RS Aggarwal - Mathematics

If<span lang="EN-RS Aggarwal - Mathematics